Antimicrobial effect of brazillian propolis/polycaprolactone polymer on some human pathogenic bacteria - Sanpa S. (2014)
The antimicrobial activities of propolis against some bacterial strains have been studied. However, there are few reports on biopolymers from propolis. Polycaprolactone (PCL) is a biodegradable polymer that has a long history of use in the biomedical field. In this work, the polymer nanofiber was grown from a Brazillian propolis extract solution on PCL using an electrospinning technique. Antimicrobial activities were investigated by the disc diffusion method. The propolis extract and polymer nanofiber could inhibit some human pathogenic bacteria. In addition, the inhibitory effects on tested microorganism depended on the concentration of propolis extract mixed with the polymer nanofiber. Such properties of the propolis/PCL nanofiners can be further developed for biomedical applications. © (2012) Trans Tech Publications.